George Aitken : inter-departmental correspondence - White, N. I.
034-0196-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER- DEPARTMENTAL CORRESPONDENCE. From N.I. White Department Research To Mr. Tewson Date 17.2.37 SUBJECT. GEORGE AIKEN I have not been able to find any particulars about this man. We have a George Aitken on our Index, but as he was born in 1868, I do not think he can be the one. He is or was a Lecturer for the International Peace Movement. I have looked up the "Daily Worker", the "New Leader" the "Tribune" and the "Socialist Leaguer" in the hope of discovering that G. Aiken was (a) a Communist or (b) connected with the same political organisations as Brailsford, but have not found any mention of him anywhere. 292/946/34/196